PELATIHAN MENJADI PEMANDU WISATA BERBAHASA INGGRIS GUNA PENGEMBANGAN DESTINASI WISATA DI DESA KARANG BUNGA - Wisnu Subroto; Melisa Prawitasari (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2022)
This training activity aims to improve the ability of local tour guides in mastering English and readiness to become guides in interacting with domestic and foreign tourists. The location of the service is located in Karang Bunga Village, Mandastana District, Barito Kuala Regency, South Kalimantan Province. The training was held in July and attended by 30 participants. The method used in the training uses the lecture method, practice, and mentoring. At the end of the training, participants are required to take an English test. The results of the training show that tour guides in the transmigration village of Karang Bunga Village get good results for areas that are newly opened natural tourist destinations. This training is carried out as an effort so that when foreign tourists visit Karang Bunga Village, the people in the village can easily explain their natural tourism.